PERAN MEDIATOR DALAM PENYELESAIAN PERKARA PERDATA DI PENGADILAN NEGERI - Devi Rianti Effendi (UNES Journal of Swara Justisia, 2019)
The court without trying to resolve it first at the nagari level through the Adat NagariKerapatan Institute (KAN). In addition to the problem of lack of trust in customary institutions, filing a case directly with the Court is considered to have a value of prestige and self-esteem in this case which makes it difficult for the Judge to attempt to reconcile parties who litigate in addition to the absence of strict regulations regarding peace efforts in the Court. Based on the description of the background above, the writer wants to conduct research and realize in a scientific work in the form of a thesis entitled "Mediator Role in Settling Civil Cases in the District Court". Regarding the background of the problem the authors mentioned above, the problems to be addressed are as follows, First, How is the Role of the Mediator in Settling Civil Cases in the District Court, Secondly, What are the factors that influence the Mediator's Role in resolving the Civil Code Case, Third, how is the power of law against the decision of peace in civil cases in the District Court. The mediator in resolving disputes in the court should prioritize the principles of an independent mediator, even though later the mediator is chosen by the parties as mediators from the judge, but also prioritized to provide opportunities for professional mediators not judges. The important role of a mediator in resolving disputes is very important and must be active in encouraging the parties to reconcile in resolving the dispute. The mediator should not get caught up in things that will cancel the peace, for example pressing one party to accept an offer from the other party. Because the results implemented do not get the meaning of the peace, and may even get new problems later. And this is where the important role of a mediator is to carry out its function to reconcile the parties. And if necessary to approach persuasively to each party separately to find a midpoint in the peace of the parties. The legal strength of the peaceful determination issued by the mediator is a decision that has binding and final legal force, and / or in other words has been inclined and there is no more legal effort taken from each party. And if there should be a new dispute related to the same object, then the Court must institutionally reject the dispute.